ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO KEUANGAN PADA PT AKHASA WIRA INTERNATIONAL TBK - Suryadi Setiawan; Sujiyati Sujiyati; Indra Subekti; Ria Prasetyaningsih; Sri Hermuningsih (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Financial reports are the main data source in assessing the Company's performance. Financial analysis is needed to find out whether the company has good financial performance or not. This research aims to show the results of the financial analysis of PT Akhasa Wira International, Tbk in 2022-2023 which is reviewed with liquidity, profitability and activity ratios. The research method used is quantitative data with data sources obtained from the company's financial reports for 2022-2023. Data collection techniques are calculated, analyzed and the results interpreted in descriptive form. The results of this study show that the CR, QR, TATO, FATO, DAR, and DER ratios show positive results. PT Akhasa Wira International Tbk shows solid financial performance in 2023, with good liquidity, profitability, solvency and activity. Keywords : Financial Report; Financial Performance; Financial Ratios